Respuesta :

A)
               Vf² = vi² + 2ad   Subtract 2ad from both sides
     Vf² - 2ad = vi²              Find the square roots of both sides
√(Vf² - 2ad) = √(vi²)         Cancel out the squares with the square roots
  Vf - √(2ad) = vi               Switch the sides to make it easier to read
                 vi = Vf - √(2ad)

B)                 Vf² = vi² + 2ad   Subtract vi² from both sides
             Vf² - vi² = 2ad           Divide both sides by 2a
    (Vf² - vi²) / 2a = d               Switch the sdies to make it easier to read
                         d = (Vf² - vi²) / 2a